El problema de asignación de frecuencias generalizado con pesos y su solución - Muñoz, David F. (2018)
We report performance of 15 heuristics and 4 metaheuristics to solve a frequency assignment problem where the value of an assigned frequency depends on the weights of the corresponding site where the frequency is assigned. Different algorithms where tested on two sets of problems, the first one corresponds to the well-known Philadelphia problems and the second one to situations similar to the assignment of FM frequencies in Mexico. Experimental results showed that the heuristics that take into account the site weights performed the best and, among the four metaheuristics tested, the algorithm based on simulated annealing performed the best.